“Optimización del proceso de extracción hidroalcohólica a partir del eneldo (Anethum graveolens) en función del contenido de polifenoles totales y actividad antioxidante”. - Silva Paredes, Jeny Mariana (2022)
Dill has various medicinal, food and cosmetic uses. To optimize the hydroalcoholic extraction process of the “Eneldo” drug; the plant was dehydrated in a forced air oven for 48 hours at 40°C. The runs were established using the Design Expert 8.0.6 program, which produced 17 experimental runs; the factors analyzed were time (6h, 15h and 24h), temperature (30°C, 45ºC and 60°C) and ethanol concentration (60%, 75% and 90%). In the phytochemical screening carried out, secondary metabolites stand out, such as: fatty compounds, triterpenes - steroids, phenolic compounds, flavonoids, quinones, mucilages and bitter principles. To quantify the content of total polyphenols and the antioxidant capacity of the different experimental runs, the Folin Ciacalteu and Frap assays were used, respectively. The optimal combination of factors that maximizes the yield of total polyphenols (12.9812 mgGAE/g) and antioxidant activity (423.998 μmolFe2+/g) is the process carried out at 7:77 H at 58.36 C with an ethanol concentration at 89.50%.